1996
DOI: 10.1530/eje.0.1350543
|View full text |Cite
|
Sign up to set email alerts
|

l-Arginine is unlikely to exert neuroendocrine effects in humans via the generation of nitric oxide

Abstract: There is now considerable evidence that nitric oxide is an important neuroregulatory agent, but there has been very little investigation of its possible role in neuroendocrine mechanisms in humans. We have investigated the effects of two nitric oxide precursors, L-arginine and molsidomine, under basal conditions on the pituitary hormones growth hormone (GH), prolactin, luteinizing hormone, follicle-stimulating hormone, thyrotrophin, adrenocorticotrophin (ACTH) and vasopressin, and also on serum cortisol; we ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
1

Year Published

1997
1997
2014
2014

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 16 publications
1
16
1
Order By: Relevance
“…Previous experiments have also reported a decrease in serum LH concentrations after systemic administration of L-AME (4). A recent study in humans has reported that the administration of L-AME was ineffective in modifying serum LH concentrations (27). However, in this study, the dose was about 0.4 g/kg bw, which is lower than the minimal effective dose in the rat.…”
Section: Discussioncontrasting
confidence: 62%
“…Previous experiments have also reported a decrease in serum LH concentrations after systemic administration of L-AME (4). A recent study in humans has reported that the administration of L-AME was ineffective in modifying serum LH concentrations (27). However, in this study, the dose was about 0.4 g/kg bw, which is lower than the minimal effective dose in the rat.…”
Section: Discussioncontrasting
confidence: 62%
“…The infusion of L-arginine enhanced plasma growth hormone [34] and glucagon levels [35]. Since these hormones are known to facilitate lipolysis, L-arginine supplementation may possibly affect fat metabolism in skeletal muscle.…”
Section: Discussionmentioning
confidence: 99%
“…Nitric oxide is a highly reactive gas that has been suggested to function as a neurotransmitter in the neuroendocrine system [7]including the somatotropic axis [15, 17, 22]. In view of these data, we have reevaluated the role of nitric oxide pathways on canine GH secretion, and more specifically analysed the role played by NO on GHRH, GHRP-6 or sumatriptan-stimulated GH secretion.…”
Section: Discussionmentioning
confidence: 99%